Effects of a ferroelectric interface on thermionic injection-induced cooling in single-heterojunction devices based on thin-film electrode/medium/electrode design. Issue 27 (22nd June 2015) - Liu, Qing; Wu, Ting; Hsiao, Yu-Che; Li, Mingxing; Hu, Dehua; Wang, Hongfeng; Xu, Hengxing; Tisdale, Jeremy; Hu, Bin
Abstract : The mechanism of phonon absorption from injected carriers is used to generate a thermionic cooling effect in organic thin-film electrode/medium/electrode devices. Abstract : This paper reports experimental studies on the effects of a ferroelectric interface on thermionic cooling in single-heterojunction electrode/medium/electrode thin-film devices by using high-dielectric MoO3 oxide and a ferroelectric P(VDF-TrFE) polymer. We observe a thermionic cooling of 0.10 °C from the single Au/MoO3 /ITO device at a low injection current of 0.50 mA cm −2 . The experimental studies at different film thicknesses and current densities suggest that this cooling effect is determined by three competing processes: phonon absorption from injected carriers through a thermionic process via charge–phonon interactions, Joule heating from the electrical transport of injected carriers, and heat transfer between charge-injecting and charge-collecting electrodes through phonon conduction. Furthermore, we find that inserting a ferroelectric polymer [P(VDF-TrFE)] interface can largely enhance the thermionic cooling from 0.10 °C to 0.20 °C by a factor of 2 in the Au/P(VDF-TrFE)/MoO3 /ITO device at a very low injection current of 0.15 mA cm −2, as compared with the Au/MoO3 /ITO device without a ferroelectric interface. Our analysis indicates that the ferroelectric P(VDF-TrFE) interface can decrease the heat transfer between charge-injecting and charge-collecting electrodes due to its low thermal conductivity but still allow a thermionic injection due to its ferroelectric polarization to enhance the cooling effect. Therefore, our work presents a new approach to enhance the thermionic cooling effect by using a ferroelectric interface in organic heterojunction thin-film electronic devices.